Agricultura de precisão: manejo da fertilidade com aplicação a taxa variada de fertilizantes e sua relação com a produtividade de culturas - Bellé, Gustavo Luiz (2009)
The agriculture of precision has been an important tool for the characterization of the spatial variability of soil attributes and crops. Thus, there is many options to elaborate thematic digital maps that can improve the soil and crop management. In this work, two croplands that has been managed with precision agriculture during several years were selected. One of them was called field Lagoa, it is a 132 ha, and the other, is field Schmidt, it is a 125 ha. In both croplands soil samples were collected with regular grid of 100 x 100 m. In the field Lagoa three soil sampled were done while in the field Schmidt two soil sampled were done along four years of evaluation. In order to investigate the crop yield variability, the yields data were collected with a combine MF34, equipped with yield sensor, GPS (Global Position System), board computer (Datavision). In the field Talhao, the yield maps were made to corn 2004/05, wheat 2005, soybean 2005/06, soybean 2006/07, corn 2007/08 and, in the field Schmidt, crop data were collected to soybean 2004/05, soybean 2005/06, soybean 2006/07 and corn 2007/08. The yield data and soil data were processed in the softwares SGIS® and Campeiro 6.0. The variable rate fertizer was done with equipment Hércules 10.000 equipped with disks system to immediate change the fertilizer rate . The evolution of soil fertility indicate that, in areas with high phosporus and potassium levels, the range of variation was maintained through the years, although, with a decrease in extreme values. The correlations of soil attributes with crop yield maps were higher in the field Schmidt mainly to CEC, Mg, organic matter, Ca, and, in the field Lagoa there was correlation, mainly, with organic matter. The match distribution and potassium the varied rate allowed that the nutrient supply was enlarged e/ou above below the export of the cultures, not interfering in the revenue. The crop yield map was an efficient tool to define yield zones driving the site specific management of fertilizers and soil management.